Trіazolo[1,5-c]quіnazolіnes Synthesis, antimicrobial and antifungal activity [quinazolin-4(3H)-ylidene]hydrazides of carboxylic acids (Message 1) - Schabelnyk, K. P.; Kholodnyak, S.V.; Berest, G.G.; Kоvalenko, S. І.; Polishchuk, N. M.; Kamyshnyі, O. M. (Zaporozhye Medical Journal, 2018)
The modern standards and algorithms of antimicrobial therapy, that ensure a high level of the treatment’s quality and prevention of the most infectious-inflammatory diseases, provide wide using of chemotherapeutic agents. However, the modern medicines do not always have satisfactory chemotherapeutic and pharmacological properties; this fact is most often associated with the resistance of microorganisms to them. That is why the creation of the new chemotherapeutic drugs by natural antibiotics’ chemical and microbiological modification, the chemical synthesis of the new substances among the various classes of organic compounds is a topical problem. The aim of the study is the developing of simple and accessible methods for the synthesis of new [quinazoline-4(3H)-ylidene]hydrazides of cycloalkyl-(hetaryl) carboxylic acids, analysis of their physical-chemical properties, antimicrobial and antifungal activity. Materials and methods. The study of the antimicrobial activity of synthesized compounds was carried out by the method of two-fold serial dilutions in the Mueller Hinton broth (for strains Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 25922, Pseudomonas aeruginosa ATCC 27853) and in the Saburo broth (for Candida albicans ATCC 885-653). Minimal Inhibitory Concentration, Minimal Bactericidal and Fungicidal Concentration were defined. Results. It was found that synthesized compounds show antimicrobial and antifungal activity to researched strains. Conclusions. There have been considered a number of preparative methods for the synthesis of [quinazoline-4(3H)-ylidene]hydrazides of cycloalkyl-(hetaryl)carboxylic acids, which are significant as chemical reagents for the preparation of condensed heterocyclic and biologically active compounds. The structure and individuality have been proved by elementary analysis and physical-chemical methods (1H NMR-spectroscopy, HPLC/MS). The antimicrobial analysis shows that N'-[quinazoline-4(3H)-ylidene]-2(3)-heteril hydrazides containing a pyridinecarboxylic acid residue in the molecule have the highest activity, which exceeds the activity of the reference standard “Trimethoprim”. N'-(6-bromohinazolin-4(3H)-ylidene)benzofuryl-2-carbohydrazide demonstrates the highest antifungal activity, which is comparable with the reference standard “Ketoconazole”.